A difficult case of the differential diagnosis of focal infiltrative lung changes in phthisiatric practice - N. L. Karpina; A. V. Antipova; L. I. Chekletsova; S. Yu. Possazhennikova; O. V. Demikhova (Вестник рентгенологии и радиологии)
Errors occur rather commonly in the differential diagnosis of respiratory diseases accompanied by X-ray lung tissue changes as foci and infiltration. Infiltrative and disseminated pulmonary tuberculosis, lung cancer, and pneumonia constitute a high proportion among the detected concurrent lung diseases. The rate of diagnostic discordance for these lung abnormalities accounts for more than 30%; and the diagnosis period for an infiltrative lung process lasts 2–3 weeks in 20% of cases and above 1–3 months in 80%. In particular, clinicians are faced with great difficulties in diagnosing aspiration pneumonia; this is due to that its X-ray manifestations are not purely specific and they are characterized by the parenchymal (alveolar) infiltration oflung tissue with a varying extent of lung inflammation.This paper describes a clinical case of a patient with salivary gland adenocarcinomaand focal infiltrative lung changes. Diagnostic difficulties have emerged in establishing the genesis of the changes in the lung.